Sodium propionate decreases implant-induced foreign body response in mice - Deivenita Juliana Alves Carvalho do Carmo; Marcela Guimarães Takahashi Lazari; Letícia Cristine Cardoso dos Santos; Pedro Augusto Carvalho Costa; Itamar Couto Guedes Jesus; Silvia Guatimosim; Pedro Pires Goulart Guimaraes; Silvia Passos Andrade; Paula Peixoto Campos (PLoS ONE, 2025)
The short-chain fatty acid (SCFA) propionate, beyond its actions on the intestine, has been able to lower inflammation and modulate angiogenesis and fibrogenesis in pathological conditions in experimental animal models. Its effects on foreign body reaction (FBR), an abnormal healing process induced by implantation of medical devices, have not been investigated. We have evaluated the effects of sodium propionate (SP) on inflammation, neovascularization and remodeling on a murine model of implant-induced FBR. Polyether-polyurethane sponge discs implanted subcutaneously in C57BL/6 mice provided the scaffold for the formation of the fibrovascular tissue. Fifteen-day old implants of the treated group (SP, 100 mg/kg for 14 days) presented a decrease in the inflammatory response as evaluated by cellular influx (flow cytometry; Neutrophils 54%; Lymphocytes 25%, Macrophages 40%). Myeloperoxidase activity, TNF-α levels and mast cell number were also lower in the treated group relative to the control group. Angiogenesis was evaluated by blood vessel number and VEGF levels, which were downregulated by the treatment. Moreover, the number of foreign body giant cells HE (FBGC) and the thickness of the collagenous capsule were reduced by 58% and 34%, respectively. Collagen deposition inside the implant, TGF-β1 levels, α-SMA and TGF-β1 expression were also reduced. These effects may indicate that SP holds potential as a therapeutic agent for attenuating adverse remodeling processes associated with implantable devices, expanding its applications in biomedical contexts.